The problem of formation of professional competence of future specialists in food technology in the implementation of dual education - Kravchenko, O.; Starova, T.; Kushniruk, N. V.; Oleynik, T.; Кушнірук, Н. В. (MAGNANIMITAS, ATTN, 2021)
The article considers the essence and structure of professional competence of specialists in food technology in terms of dual education. The relevance of professional competence as an indicator of readiness to perform professional tasks, solving problems of production activities is substantiated. Among the important components of the professional competence of a food technology specialist, there are research, professional, integrative, instrumental, motivational and socio-personal competencies. These competencies reflect the readiness of future specialists in food technology to perform the tasks of professional activity. It is emphasized that modern education needs to update the educational forms and methods that determine the high level of training and motivation of future professionals, their adaptation to the conditions of production. One of the innovative forms of realization of the educational process is dual education. Among the main tasks of dual education, there are the following: formation and development of professional competence and personal qualities of future specialists in food technology to solve applied educational problems, overcoming the discrepancy between theoretical and practical training of graduates, strengthening cooperation between educational institutions and employers.
Keywords: Competence; Dual education; Food technology; Professional development